Analysis Of Marketing Strategy In Hospital Health Institutions: A Systematic Literature Review - Linda Ayu Mustikasari; Farid Agushybana; Septo Pawelas Arso (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Marketing is one of the important functions in organizations, including hospital health institutions. Marketing can help hospitals to achieve their goals, such as increasing public awareness, increasing demand for hospital services, and increasing customer satisfaction. The purpose of this study is to examine marketing strategies used in hospital health institutions through a systematic literature review. This research used the Systematic Literature Review (SLR) method. Research data was collected from literature published in reputable scientific journals. The literature was collected through searches in electronic literature databases, such as Google Schoolar and Scopus. The collected data were then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that hospital marketing strategies include digital marketing, offensive strategies, preparation and determination of the marketing mix, intensify strategies, and 4P (Product, Price, Place, Promotion).